Penerapan Strategi Cooperative Learning Tipe Stad (student teams achievement division) untuk Meningkatkan Hasil Belajar dalam Materi Ciri-Ciri Makhluk Hidup Siswa Kelas III SDN 2 Ardirejo Kepanjen - Winarsi, Winarsi (Universitas Nahdlatul Ulama Pasuruan, 2022)
This study aims to describe the application of a cooperative learning strategy type STAD (Student Teams Achievement Division) to improve learning outcomes in the material characteristics of living beings of third grade students of SDN 2 Ardirejo Kepanjen, and to determine the improvement of learning outcomes in the material characteristics of students' living things. class III SDN 2 Ardirejo Kepanjen by implementing the STAD strategy. This research is an action research with 2 cycles and in each cycle there are 4 stages consisting of planning, action, observation and reflection. The data collected came from the results of the test and the results of observations and were analyzed using a descriptive approach. The results showed that the results of the implementation of the STAD strategy could improve the learning outcomes of third grade students at SDN 2 Ardirejo Kepanjen. Completeness of students in the first cycle is 17.4% and in the second cycle is 100%.